2011
DOI: 10.1634/theoncologist.2011-0141
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab Plus FOLFIRINOX (ERBIRINOX) as First-Line Treatment for Unresectable Metastatic Colorectal Cancer: A Phase II Trial

Abstract: Background. Triplet chemotherapy has demonstrated manageable toxicities and a favorable response rate. The addition of cetuximab to chemotherapy can increase treatment efficacy. We evaluated the efficacy and safety of cetuximab plus 5-fluorouracil, leucovorin, irinotecan, and oxaliplatin (FOL-FIRINOX), the ERBIRINOX regimen, as first-line treatment in patients with unresectable metastatic colorectal cancer (mCRC).Patients and Methods. In a phase II study, treatment consisted of weekly cetuximab plus biweekly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
68
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 28 publications
0
68
1
1
Order By: Relevance
“…Such treatment has become the standard first-line therapy for oligometastatic CRC patients when there is a possibility of surgery of metastases [33]. The association with bevacizumab [34] and cetuximab [35] was tested in a phase II trial and demonstrates impressive efficacy. The efficacy of triplet chemotherapy without biotherapy was tested in some patients previously pretreated with either oxaliplatin or irinotecan in a phase I study.…”
Section: Discussionmentioning
confidence: 99%
“…Such treatment has become the standard first-line therapy for oligometastatic CRC patients when there is a possibility of surgery of metastases [33]. The association with bevacizumab [34] and cetuximab [35] was tested in a phase II trial and demonstrates impressive efficacy. The efficacy of triplet chemotherapy without biotherapy was tested in some patients previously pretreated with either oxaliplatin or irinotecan in a phase I study.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the use of FOLFOXIRI plus cetuximab or pani tumumab achieved remark able results in terms of anti cancer activity and secondary resection rates. Promising evidence of the clinical activity of three-drug chemo therapy plus cetuximab regimens was initially observed in mol ecularly unselected populations in the POCHER, ERBIRINOX and COFI trials (ORR of 79%, 81%, and 75%, respectively), [61][62][63] and then replicated in patients with wild-type KRAS exon 2. 64,65 For example, the phase II trial by Saridaki and colleagues, 64 which evaluated a modified FOLFOXIRI regimen plus cetuximab in 30 patients with KRAS-exon-2-wild-type mCRC, reported an ORR and a radical resection rate of 70% and 37%, respectively.…”
Section: Combination With Anti-egfr Agentsmentioning
confidence: 99%
“…As yet, there is no established standard of care for the neoadjuvant treatment of resectable, borderline or locally advanced PDAC. Recently the standard of care in the metastatic setting has been improved by the FOLFIRINOX protocol [12], a combination of 5-fluorouracil (5-FU), leucovorin, irinotecan and oxaliplatin that was first examined in colorectal cancer [13,14] and by the combination of gemcitabine plus nanoparticle albumin-bound paclitaxel (nab-paclitaxel) [15]. Both regimens are superior to the standard of single-agent gemcitabine [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from conventional chemotherapies, various targeted therapies including anti-EGFR, anti-VEGF and anti-Her2 antibodies have become the standard of care for certain types of colorectal or gastric cancer [13,16,17,18,19]. However, despite numerous large clinical trials, no targeted therapy has as yet demonstrated clinical benefit in PDAC apart from the tyrosine kinase inhibitor erlotinib in combination with gemcitabine [20].…”
Section: Introductionmentioning
confidence: 99%